Vrednotenje Intervjuja kontinuitete življenja pri osebah po možganski kapi - Janša, Jelka (Rehabilitacija (Ljubljana), 2008)
Background: Continuity of life is a novel concept in rehabilitation. Therefore, we performed psychometric evaluation of the Continuity of Life Interview in chronic stroke patients. Methods: Thirty randomly chosen stroke patients participated, 11 females and 19 males. In addition to COLI, Barthel Index and WHO DAS-S were applied at first assessment. During the first interview, another assessor was present independently doing the scoring. Three days later, a third assessor performed the interview with the same person. Results: Internal consistency was found to be satisfactory (Cronbach ranging from 0.61 to 0.80; all P<0.001). Agreement between assesors was also statistically significant (r values from 0.63 to 0.93; all P<0.001). Conclusions: COLI is a reliable assessment tool, indicating correlation of continuity of life with disease duration, education and marital status.
Keywords: možganska kap; rehabilitacija; vocational rehabilitation; kontinuiteta življenja; ocenjevalne lestvice; zanesljivost; veljavnost